The Improvement of Jump Height and Limb Muscle Power Using Self-Training Split Squat and Lateral Jump in Basketball Player of Familia Surabaya Age Group-15 During the Covid-19 Pandemic - Rigan Deri Wicaksono; Himawan Wismanadi; Gigih Siantoro (BIRCU, 2021)
The research aims to analyze the effect of split squat jump practice and lateral jump practice on jump height and leg muscle power. Besides, it is to analyze the most influencing practice between split squat jump practice and lateral jump practice on jump height and led power muscle. The method used in the research is quantitative using the quasi-experimental method. The research design used is pretest and posttest which are divided into three groups, group I as split squat jump, group II as lateral jump, and control group. The data analysis is ANOVA. The data collection is done by testing jump height using vertical jump test and limb muscle power test using jump MD tool while pretest and posttest. The data is analyzed by using SPSS 22.0 series. The result of Paired sample T-test shows that each variable is obtained sig 0,000<0,05 from the jump height and paired sample T-test of limb muscle power. It indicates that there is a significant effect or differences of pretest and posttest from the dependent variable between jump height and limb muscle power. The ANOVA result of strength and limb muscle power shows the jump height, F: 3,874, sig 0,040, power F: 4,829, sig 0,017. It can be concluded that there is a significant difference in the result of jump height and limb muscle power in three different groups which is sig <0,05.